“Fistula Zero” Project After Total Laryngectomy: The Candiolo Cancer Institute Experience - Crosetti, Erika; Arrigoni, Giulia; Sprio, Andrea Elio; Succo, Giovanni (Frontiers in Oncology, 2021)
Objectives: Pharyngocutaneous fistula (PCF) is a troublesome complication after total laryngectomy. The “Fistula zero” project aims to reduce the number of PCF by following a detailed protocol based on three fundamental key points. Materials and Methods: The Fistula zero project included 77 patients who underwent total laryngectomy in the period from January 2019 to December 2020. The protocol consisted of three main aspects: the systematic placement of a Har-El salivary bypass tube; the continuous horizontal watertight pharyngeal suture using a barbed suture; onlay insetting of a pedicled flap in pre-treated patients. Results: One case of PCF (1.3%) and three small blind fistulas (3.9%) were observed in this series. The mean length of hospitalization was 18 days. Conclusion: Pharyngocutaneous fistula (PCF) prolongs hospitalization and delays adjuvant treatments. Thanks to a strict adherence to the protocol, it was possible to reduce PCF rates, avoiding lengthy hospitalization and additional surgical procedures.